A cohort analysis of sexually transmitted infections among different groups of men who have sex with men in the early era of HIV pre-exposure prophylaxis in France - Christina K. Psomas; Guillaume Penaranda; Frederique Retornaz; Hacene Khiri; Marion Delord; Philippe Halfon; Patrick Philibert (Elsevier, 2022)
Background: MSM are at particular risk of STIs due to sexual behavior and substance use. HIV PrEP use may increase this risk. Design: Our aim was to comparatively assess incident STIs among different at-risk groups-PLWHIV, HIV-negative PrEP and no-PrEP users-seen at our center early after PrEP implementation. Methods: Clinical data were retrospectively collected on 636 MSM seen at the Infectious Diseases Department between September 2016 and October 2018. STI incidence rate was assessed among groups for the whole period, as well as separately for each year of the study. Results: Overall STI incidence rate ratio was higher in HIV-neg when compared to PLWHIV. In multivariate analysis, STI risk was significantly higher among HIV-neg no-PrEP users compared to PLWHIV, while not different between PLWHIV and PrEP users.STI incidence globally increased during the first 2 years after PrEP approval among PLWHIV and no-PrEP users, stated by odds ratio (OR = 1.77 [1.23-2.55], p = 0.0020 and OR = 2.29 [0.91-5.73], p = 0.0774 respectively) while it remained rather stable for HIV-neg PrEP users (OR = 1.19 [0.60-2.38], p = 0.6181). The HIV-neg no-PrEP group remained at higher risk of STI than PLWHIV and PrEP users during the two periods. Conclusion: These results suggest that a proactive approach of an efficient follow-up of MSM participants since PrEP approval may have prevented an increase of the incidence of STIs among PrEP users.